A Comparative Study of Genetic Diversity in Chickpea Based Upon Touchdown and Non-touchdown PCR Using ISSR Markers - Mahesh Kumar" (Science Faculty of Chiang Mai University, 2019)
Chickpea is one of the world’s most important but less studied leguminous food crops. In the present study, inter simple sequence repeat (ISSR) marker were employed to investigate genetic diversity of chickpea. Eighteen cultivars of chickpea were studied using six ISSR markers out of these three markers (GTG)5, (GTGC)4 and (TCC)5 were found to generate reproducible DNA fragments. On an average 3 or more bands ranging from 0.25-3.0 kb were obtained in case of non touchdown PCR while in case of touchdown PCR 2 bands ranging from 0.25-4.0 kb were obtained. The cophenetic correlation coefficient (r) for non touchdown and touchdown PCR was found to be 0.79 and 0.9 respectively. For the selection of good parental material in breeding programs, the genetic data produced through the present study can be used to correlate with the relationships between morphological traits.